2023
DOI: 10.3390/ijerph20043494
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and COVID-19 among Older African American Adults: A Scoping Review of Healthcare Access and Resources

Abstract: African American/Black communities comprise 12.2% of the U.S. population, with a COVID-19 infection rate of more than 18% and marginal access to healthcare services. This scoping review synthesizes the emerging evidence on healthcare accessibility among older African American adult communities with dementia and COVID-19, as well as the resource requirements for this population during the pandemic. Searches of different databases for empirical studies and other sources on dementia and COVID-19 among older Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For example, older African American adults with dementia and COVID-19 were described to experience systemic discrimination, increased delays, and reduced access to healthcare resources such as ventilators, technological supports (e.g., cell phones), transportation, health insurance, and access to intensive care units during COVID-19 ( 28 ). Moreover, African American adults often experienced distrust towards the healthcare system and the government due to prejudice, fear, racism, and discrimination ( 28 ). Consequently, a lack of trust was related to the information spread by institutions such as the media and the government ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, older African American adults with dementia and COVID-19 were described to experience systemic discrimination, increased delays, and reduced access to healthcare resources such as ventilators, technological supports (e.g., cell phones), transportation, health insurance, and access to intensive care units during COVID-19 ( 28 ). Moreover, African American adults often experienced distrust towards the healthcare system and the government due to prejudice, fear, racism, and discrimination ( 28 ). Consequently, a lack of trust was related to the information spread by institutions such as the media and the government ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a study by Wang et al found that African American dementia patients have an almost threefold increase in the adjusted odds ratio of becoming infected with COVID-19 [ 8 ], and their prevalence is nearly double compared to white American patients (19% vs. 10%) [ 9 ]. In a scoping review, Udoh et al showed that African American patients with dementia and COVID-19 had longer delays in accessing healthcare services, including ICU access, mechanical ventilation, or transportation [ 10 ]. In Europe, the Roma population has been suggested to have an increased risk of COVID-19 [ 11 ], but clinical results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%